Makna ummatan wasathâ Penafsiran Q.S Al-Baqarah : 143 - Ahmad Ramadhan; Adha Saputra; Alber Oki (ZAD Al-Mufassirin)
Being a polemic in the midst of the ummah is how to be a person who can balance not only in the worldly aspect but also from the ukhrowi aspect, not exaggerating in doing something and not taking things lightly, so actually this polemic has been explained in Islam which is a ummah. the middle itself, then for those who embellish the Qur'an, he will find these concepts. The choice of the theme above is intended to clearly explain the concept of being a middle ummah in accordance with the correct understanding. Qs. Al-Baqarah [1]: 143, using a library research approach by analyzing the words of classical and contemporary commentators and refining the correct words (tarjîh), as will be found deviations in the meaning of wasatâ ummatan itself then to find the ultimate truth the above theme is very important to discuss, from this research, it will be known how the correct concept of being a middle class, which can be a guide for every Muslim to live his life. And so also make every human being who believes in worshiping the Qur'an Al-'Azhim.